2014
DOI: 10.1186/1475-2875-13-309
|View full text |Cite
|
Sign up to set email alerts
|

In vivo efficacy of artemether-lumefantrine and artesunate-amodiaquine for the treatment of uncomplicated falciparum malaria in children: a multisite, open-label, two-cohort, clinical trial in Mozambique

Abstract: BackgroundMozambique adopted artemisinin-based combination therapy (ACT) for the treatment of uncomplicated Plasmodium falciparum malaria in the year 2006, and since 2009 artemether-lumefantrine (AL) and artesunate-amodiaquine (ASAQ) have been proposed as alternative first-line treatments. A multicentre study was conducted in five sites across the country to assess the in vivo efficacy and tolerability of these two drugs.MethodsChildren aged six to 59 months with uncomplicated malaria were recruited between Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 17 publications
12
21
1
Order By: Relevance
“…Overall, the corrected efficacies for both AL and ASAQ are consistent with findings from other studies conducted in Malawi and elsewhere in the region [ 3 , 5 , 11 13 ]. In a therapeutic efficacy study conducted in 2010 in six study sites across Malawi, the combined PCR-corrected ACPR for AL was 93.4 % [ 3 ].…”
Section: Discussionsupporting
confidence: 89%
“…Overall, the corrected efficacies for both AL and ASAQ are consistent with findings from other studies conducted in Malawi and elsewhere in the region [ 3 , 5 , 11 13 ]. In a therapeutic efficacy study conducted in 2010 in six study sites across Malawi, the combined PCR-corrected ACPR for AL was 93.4 % [ 3 ].…”
Section: Discussionsupporting
confidence: 89%
“…The study showed that PCR-uncorrected cure rates for AS-AQ were 98 % (95 % CI 89.4, 99.9) in the forest zone and 97.3 % (95 % CI 90.7, 99.7) in the savannah zone whilst AL showed PCR-uncorrected cure rates of 85 % (95 % CI 77.5, 90.9) in the forest zone and 56.3 % (95 % CI 37.7, 73.6) in the savannah zone. Although the study was not a comparative study, the findings compare well with the observation of higher PCR-uncorrected cure rate for AS-AQ, compared with AL, in Mozambique [ 20 ]. This observation may be explained by the longer terminal half-life of amodiaquine (approximately 10 days) over lumefantrine (approximately 4 days) resulting in a higher post-treatment prophylactic effect of AS-AQ [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 64%
“…Our observation is consistent with those in previous reports from Kenya [ 36 ], Angola [ 37 ], Mozambique [ 37 ], Senegal [ 39 ], Ugandan [ 40 ] as well as other areas of Sub-Saharan Africa [ 30 ], Caribbean’s Haiti [ 41 ], and South Asia’ Bangladesh [ 42 ], where the K13-propeller gene mutations associated with artemisinin resistance were absent. Additionally, trials of ACT for treating uncomplicated P. falciparum malaria in Uganda [ 43 ], Kenya [ 44 ], and Mozambique [ 45 ] have found 28-day PCR-corrected cure rates of 89 % or greater. Thus, our data is strongly suggesting that many Grande Comore P. falciparum isolates collected in 2013–2014 are likely still sensitive to artemisinin even under the drug selective pressure from introduction of ACT as the first-line treatment since 2004.…”
Section: Discussionmentioning
confidence: 99%